Aktualisasi Pemikiran Bustanul Arifin Tentang Politik Hukum Islam di Indonesia - Itmam, Muhammad Shohibul (POLITEA, 2020)
This paper explains the actualization of Bustanul Arifin thought on the politics of Islamic law in Indonesia which aims to find out first, how the epistemology of Bustanul Arifin thoughts on Indonesian  Islamic law and scond, how the actualization of Indonesian Islamic law politics from Bustanul Arifin's perspective. This research is a library research or library research, which is carried out by collecting library data by using a critical social and political approach. The research concludes that first, the epistemology used by Bustanul Arifin is to position the Koran and al-Sunnah as the main sources in Islamic law and the development of legal values in the Koran and al-Sunnah using the Ijmak and Qiyas methods in Islamic law. Second, the actualization of Islamic law politics Bustanul Arifin's thought is to elaborate Islamic law with positive law through the transformation of Islamic law in state legislation and institutions, so that there is a union between Islamic law and State law within the framework of State institutions which he calls the institutionalization of Islamic law. Thus, the step that needs to be developed is to determine an institution that is in accordance with the principles and values of Islamic law in the Indonesian context.